CLASSIFICATION OF THE REAL INFINITE SIMPLE AND REAL INFINITE PRIMITIVE LIE ALGEBRAS - Shnider, Steven (1969)
In this paper the real infinite simple and real infinite primitive Lie algebras are classified.